PSYCHOPHYSIOLOGICAL AND LINGUISTIC FOUNDATIONS OF THE THEORETICAL STUDY OF SPEECH DEFECTS - Makhmudova Madinakhan Sobirkhanovna; Erkaboyeva Ozoda (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the psychophysiological and linguistic foundations of the theoretical study of speech defects, the characteristics, function, structure and ways of development of the language have an important place in special pedagogy, the opinions that language is one of the necessary conditions for thinking, and that it is important in the development of society. z is reflected.